Analysis of Income Level and Profit of Salt Farming Business - Budiman, Arief (Universitas Negeri Semarang, 2022)
The purpose of this study was to determine the income level of salt farmers and the relative profit of farming in Dresi Kulon Village. The sampling technique used is purposive sampling. The data used are primary data and secondary data. The analysis used is income analysis and relative profit analysis. The results showed that the average income level of salt farmers on 0.5 – 1.5 hectares of land was IDR 400,000 per season and IDR 9,250,000 per year. The average income level on an area of ​​1.6 – 2 hectares is IDR 450,000 per season and IDR 10,400,000 per year. In the 2.1 – 3 hectares cluster, the average income is IDR 530,000 per season and IDR 12,242,000 per year. The results of the analysis show that farming is said to be profitable, but the BEP price for the entire land obtained is Rp. 203 per year. The relative advantage of the R/C Ratio of agricultural businesses is said to be profitable, while the BEP Production value in the entire land area is at a loss. The ROI value in salt farming is 50% per season and 47% per year. Tujuan dari penelitian ini adalah untuk mengetahui tingkat pendapatan petani garam dan keuntungan relatif usahatani di Desa Dresi Kulon. Teknik pengambilan sampel yang digunakan adalah purposive sampling. Data yang digunakan adalah data primer dan sekunder. Analisis yang digunakan adalah analisis pendapatan dan analisis laba relatif. Hasil penelitian menunjukkan bahwa rata-rata tingkat pendapatan petani garam pada lahan 0,5 – 1,5 hektar adalah Rp 400.000 per musim dan Rp 9.250.000 per tahun. Dalam cluster 2,1 – 3 hektar, pendapatan rata-rata adalah Rp 530.000 per musim dan Rp 12.242.000 per tahun. Hasil analisis menunjukkan bahwa usahatani dikatakan menguntungkan, namun Harga BEP untuk seluruh lahan yang diperoleh sebesar Rp 203 per tahun. Keuntungan relatif R/C Ratio usaha pertanian dikatakan menguntungkan, sedangkan nilai BEP Produksi di seluruh luas lahan merugi. Nilai ROI pada usahatani garam 50% per musim dan 47% per tahun.